St. Paul's Architecture : A History - Hess, Jeffrey A. (Book collections on Project MUSE., 2006)
From the grand boulevard of Summit Avenue to the gleaming State Capitol, St. Paul's Architecture presents more than 225 notable surviving buildings and the history of several neighborhoods in the city. With historical photographs and illustrations, this engaging book is a valuable resource not only for those interested in architectural heritage but also for anyone who admires St. Paul's unique beauty and charm.